One-pot cascade conversion of renewable furfural to levulinic acid over a bifunctional H3PW12O40SiO2 catalyst in the absence of external H-2 - Nandiwale, Kakasaheb Y.; Vishwakarma, Mona; Rathod, Simmy; Simakova, Irina; Bokade, Vijay V. (Energy & Fuels, 2021)
The conversion of biomass-derived furfural (FUR) to levulinic acid (LA), a versatile platform chemical, involves catalytic hydrogenation of FUR followed by acid hydrolysis to LA. However, this two-step process demands expensive separation and purification of the furfuryl alcohol (FAL) intermediate. Herein, we demonstrate an ingenious catalytic strategy for the one-pot cascade conversion of FUR to LA over a bifunctional catalyst without using pure external H-2. Isopropyl alcohol (IPA) served a dual role as a hydrogen donor and solvent while inhibiting the side reactions. Catalysts with a tunable surface area and acidity were synthesized by impregnating different percentages of H3PW12O40 (heteropolyacid) over a SiO2 support. The bifunctionality of the H3PW12O40/SiO2 catalyst is ascribed to the mutual coexistence of Lewis and Brvinsted acid sites. The Lewis acid sites imparted by active W metal sites adsorb hydrogen proton for catalytic transfer hydrogenation of FUR to FAL, while the predominant Brvinsted acid sites catalyze the hydrolysis of FAL to LA. Consequently, H3PW12O40/SiO2 revealed to be a potential catalyst producing an similar to 51% LA yield under optimized reaction conditions. Moreover, the catalyst was found to be reusable for three catalytic cycles. This study paves the way to develop future biorefinery, particularly direct conversion of FUR to LA over a bifunctional catalyst with a liquid H-donor, in an environmentally benign manner and comply with the green chemistry principles.